31‐4: Novel Inorganic Electron Injection and Transport Materials Enabling Large‐Sized Inverted OLEDs Driven by Oxide TFTs. Issue 1 (May 2016) - Hosono, Hideo; Kim, Junghwan; Kamiya, Toshio; Nakamura, Nobuhiro; Watanabe, Satoru
Abstract : Inverted OLEDs are fabricated using two novel transparent amorphous oxide semiconductors, C12A7 electride with work function of 3.0eV for EIL and ZnO‐based materials with 3.5eV for ETL. Both materials form an Ohmic contact with conventional cathode (ITO or Al). The performance of inverted devices employing these two materials is superior to that of normal type with conventional LiF/Al cathode. This material combination enables fabrication processes involving an exposure to ambient atmosphere.